2012
DOI: 10.1016/j.janxdis.2012.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Contextual factors and anxiety in minority and European American youth presenting for treatment across two urban university clinics

Abstract: The current study compared ethnic minority and European Americanclinically-referred anxious youth (N = 686; 2–19 years) on internalizing symptoms (i.e., primary anxiety and comorbid depression) and neighborhood context. Data were provided from multiple informants including youth, parents, and teachers. Internalizing symptoms were measured by the Multidimensional Anxiety Scale for Children, Child Depression Inventory, Child Behavior Checklist and Teacher Report Form. Diagnoses were based on the Anxiety Disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 72 publications
1
10
0
Order By: Relevance
“…As reported previously (Beidas et al, 2012), the RM-ANOVA demonstrated that there was a main effect of time such that therapist adherence ( F (2, 222) = 100.21, p < .001) and skill ( F (2, 222) = 79.90, p <.001) improved after receiving the training and consultation package.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…As reported previously (Beidas et al, 2012), the RM-ANOVA demonstrated that there was a main effect of time such that therapist adherence ( F (2, 222) = 100.21, p < .001) and skill ( F (2, 222) = 79.90, p <.001) improved after receiving the training and consultation package.…”
Section: Resultssupporting
confidence: 79%
“…This is curious given that these individuals sought out this type of specialty training and reported that they either currently or planned to treat anxious youth in the future. This may be potentially due to difficulty identifying “pure” anxiety cases in community settings (Beidas et al, 2012; Ehrenreich-May et al, 2010; Southam-Gerow, Silverman, & Kendall, 2006). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical findings support this perception, given that comorbidity rates are often high across psychological disorders, particularly for anxiety disorders (33,34). Compared with youths in the general population, anxious youths in the community often present with multiple comorbid diagnoses, lower socioeconomic status, and a background from more disadvantaged neighborhoods (23,35,36). Therefore, future training and consultation for providers working in community settings should include practical tips on how to address issues relevant for youths from urban communities.…”
Section: Discussionmentioning
confidence: 99%
“…We included the following neighborhood socioeconomic indicators in our analyses: the percentage of individuals living below the poverty level, the percentage of individuals over the age of 25 with only a high school education/equivalent or less, the median household income, and the percentage of owner‐occupied housing units. These indicators are frequently used in studies examining neighborhood context and were chosen specifically in other investigations examining SES and psychopathology (Beidas et al, ; Stockdale et al, ; U.S. Census Bureau, ).…”
Section: Methodsmentioning
confidence: 99%